A Five-Year Strategic Financial Plan for Philippine Seven Corporation - Berdolaga, Patricia Anne B., Cinco, Kate Vivien U., Jimenez, Milyn O., Lazaro, Patricia Aubrey M., Mendoza, Arnold Christian E., Pelayo, John Rainier D., Zafe, Joshua S. 4 0 16; 5 (2024)
Abstract This research provides a thorough analysis of Philippine Seven Corporation's (7-Eleven Philippines) financial and operational performance over the past five years, focusing on inventory management, profitability, liquidity, and overall financial stability. The evaluation leverages financial data from audited statements and key financial ratios to assess the company's challenges and areas for improvement, particularly in its inventory practices and their impact on its operational efficiency and financial health. Philippine Seven Corporation operates as the master franchise holder of 7-Eleven convenience stores in the Philippines, serving as a leading player in the convenience-retail sector. Known for its extensive network of stores and a diverse range of products, the company has maintained a strong foothold in the convenience retail industry. However, recent analyses have highlighted inefficiencies in inventory management, such as the absence of a Reordering Point (ROP) system, which has contributed to operational delays and unnecessary costs. To address these challenges, the report recommends the adoption of updated inventory management solutions, including real-time inventory synchronization through modern Point of Sale (POS) systems. These strategies aim to optimize inventory turnover, enhance demand forecasting, and improve sales. By using these solutions, 7-Eleven Philippines can strengthen its operational capabilities, boost customer satisfaction, and secure sustainable financial growth in a competitive market. Keywords: Philippine Seven Corporation, Merchandise Inventory Turnover, Equity Turnover, Point of Sale, Real time inventory synchronization.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2